PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Wahyudin1, LCA. Robin Jonathan2, Ivana Nina Esterlin Barus3, Wahyudin1, LCA. Robin Jonathan2, Ivana (EKONOMIA, 2018)
Wahyudin: The Influence of Liquidity And Profitability To Stock Prices On The Indonesia Stock Exchange Companies Listed In Bei Food and Beverage Sectors. Robin Jonathan and Ivana Nina Esterlin Barus.Movement of price an share cannot be estimated surely, price a[n share determined according to supply and demand law (strength of suplly-demand) more and more one who buy share hence the share price tend to will make a move to go up. On the contrary, more and more people sell share hence the share price tend to will make a move to go down.This study aims to determine the effect of: 1) current ratio on stock prices on food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange 2) net profit margin on stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange . 3) the current ratio and net profit margin simultaneously on stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange.The population in this study are all food and beverage manufacturing companies listed on the Indonesia Stock Exchange. Any annual financial statements audited by auditors in 2013-2016 for 4 years. The results of the study conclude: 1) that Ha is rejected then it means that Current Ratio does not have a negative and insignificant effect on stock prices in the food and beverage sector companies in the Indonesia Stock Exchange; 2) Ha is accepted, it means that Net Profit Margin has a positive and significant effect on stock prices in the food and beverage sector companies in the Indonesia Stock Exchange; 3) Ha is accepted, it means that Net Profit Margin and Current Ratio have a positive and insignificant effect on stock prices in the food and beverage sector companies in the Indonesia Stock Exchange.